2019
DOI: 10.31871/wjrr.8.2.13
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Obesity and Bariatric Surgery: a Community-Based Study in Buraydah City, Saudi Arabia

Abstract: Background. Saudi Arabia (SA) has been widely involved in the epidemic of obesity. In 2016, World statistics showed that SA was highly ranked in obesity with a prevalence of around 34%. Management of obesity can include lifestyle changes, medications, or Bariatric Surgery (BS). BS has been shown to be effective intervention for weight loss, diabetes management, Dyslipidemia, and reducing mortality risk. Accordingly, this study aimed to assess knowledge and awareness of Buraydah Community about obesity with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
4
0
0
Order By: Relevance
“…In this study of Saudi adults in the Al-Qassim Region, the BMI of nearly 43.50% (n=414) of the respondents was within the normal range, while 49.1% (n=467) were classified as overweight or obese. This prevalence is consistent with that of another study in the region that found that the prevalence of obesity and being overweight was 53.5% [ 13 ]. Further, it is consistently compared to other studies that have shown that the prevalence of obesity and being overweight were 57.7%, 40%, and 54%, respectively, among adults across Saudi Arabia [ 14 - 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study of Saudi adults in the Al-Qassim Region, the BMI of nearly 43.50% (n=414) of the respondents was within the normal range, while 49.1% (n=467) were classified as overweight or obese. This prevalence is consistent with that of another study in the region that found that the prevalence of obesity and being overweight was 53.5% [ 13 ]. Further, it is consistently compared to other studies that have shown that the prevalence of obesity and being overweight were 57.7%, 40%, and 54%, respectively, among adults across Saudi Arabia [ 14 - 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, 76.50% (n=756) of them believe that the factors of an idle and lazy life, eating too much (75.60%, n=747), disease of all kinds (41.70%, n=412), stress and tension (34.60%, n=342), and psychological diseases (39.00%, n=385) can increase the risk of obesity. In comparison, our finding is consistent with those in local studies in Riyadh City published in January 2018 and in the Al-Qassim Region published in February 2019, in which the authors found that most of the respondents have a high level of knowledge about obesity’s causes and risk factors [ 13 , 16 ]. Another national study showed that the stereotype perceived most commonly was that obese individuals are lazy, which 62% of their sample endorsed [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations